Improved Delivery of Library Materials: The Cleveland Experience - Herling, J. P.; Beeler, M. G. Fancher; Reisman, A.; Dean, B. V. (Information Technology and Libraries, 1974)
This paper describes a project designed to improve services to library users by solving, through the application of operations research methods, a complex problem of delivery of library materials in an urban, multisystem library service region. Unique features, methodology, results, and limitations are discussed.